2012
DOI: 10.1111/j.1365-2265.2012.04507.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic factors affecting adequacy of thyroid nodule fine‐needle aspiration cytology

Abstract: Some ultrasonographic features suggestive of malignancy may be predictive of inadequate cytology. Patients must be notified that the FNA report may be nondiagnostic and that this represents a limitation of the technique related to the structure of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 12 publications
3
38
4
Order By: Relevance
“…These results are consistent with those of a previous study investigating radiologist-performed US-FNAC. 16 Interestingly, tumors located in the left neck were more associated with inadequate sampling in our study, although the statistical significance was not verified (p = 0.060). This finding may be related to the surgeon's position and handedness.…”
Section: Discussioncontrasting
confidence: 72%
“…These results are consistent with those of a previous study investigating radiologist-performed US-FNAC. 16 Interestingly, tumors located in the left neck were more associated with inadequate sampling in our study, although the statistical significance was not verified (p = 0.060). This finding may be related to the surgeon's position and handedness.…”
Section: Discussioncontrasting
confidence: 72%
“…Other studies confirm what we experience in daily practice: blood contamination is one of the main qualitative reasons for nondiagnostic thyroid cytology, and FNA of a hypervascular nodule will often result in bloody aspirates [4,19]. Strong intranodular vascularization is rarely mentioned in the literature as a predictor of nondiagnostic cytology [31]. It is, however, described as a possible predictor of malignancy, emphasizing the need for adequate cytology [7,12,32].…”
Section: Discussionmentioning
confidence: 51%
“…This led to the high proportion of malignancy and suspicious of malignancy (20.3%) compared with other reports (Cavaliere et al, 2009). It has been reported that thyroid nodules with a diameter <10 mm were more frequently non-diagnostic (Grani et al, 2013). In view of this, the number of non-diagnostic nodules in our study (20.9%) was receivable.…”
Section: Discussioncontrasting
confidence: 44%
“…Many scholars have focused on the valuable role of US features as predictors of malignancy (Iannuccilli et al, 2004;Kang et al, 2004;Kim et al, 2008;Lee et al, 2011;Vinayak et al, 2012;Kim et al, 2013a;Kim et al, 2013b). Currently, there is no internationally acknowledged guideline of selecting which thyroid nodules for biopsy, especially for the subcentimeter-sized ones (Iannuccilli et al, 2004;Grani et al, 2013;Kim et al, 2013a;Nixon et al, 2013). Many institutions now apply ultrasound-guided FNAB just on nodules larger than 1 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%